2022
DOI: 10.1039/d2nj02989h
|View full text |Cite
|
Sign up to set email alerts
|

Product selectivity in the photoreaction of aryl sulfonates and mesylate of estrone derivatives in sustainable and micellar media: a steady-state investigation

Abstract: Preparative and mechanistic studies on the photochemical reaction of a series of aryl sulfonates and mesylate of estrone and 17-norestrone derivatives in confined and sustainable micellar environment under steady-state conditions...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Therefore, collecting the whole results described before clearly demonstrated that the photo-Fries rearrangement reaction of esters 1 – 5 that takes place from the singlet excited state S 1 and the triplet excited state T 1 is not involved in the photoreaction. Moreover, this photochemical reactivity was also observed for 3-acyl and 3-aryl/alkylsulfonyl estrone derivatives where the singlet state was demonstrated to be the photo reactive excited state of this kind of compounds …”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Therefore, collecting the whole results described before clearly demonstrated that the photo-Fries rearrangement reaction of esters 1 – 5 that takes place from the singlet excited state S 1 and the triplet excited state T 1 is not involved in the photoreaction. Moreover, this photochemical reactivity was also observed for 3-acyl and 3-aryl/alkylsulfonyl estrone derivatives where the singlet state was demonstrated to be the photo reactive excited state of this kind of compounds …”
Section: Resultsmentioning
confidence: 62%
“…Lumiestrone 10 was also detected in the reaction mixtures of esters 1 – 4 in very low yields when the photoreaction was carried out in both solvents with the exception of the cases of esters 1 and 4 in methanol where compound 10 was formed in 22 and 30% yields, respectively. Epimerization of the methyl group at C-13 of estrone 6 accounts for the formation of lumiestrone because a Norrish Type I is involved during the photochemical reaction and competes with the photo-Fries rearrangement process. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation